Artificial Intelligence / Wan Dorishah Wan Abdul Manan (Universiti Teknologi MARA, Terengganu, 1992)
Artificial Intelligence (AI) is a relatively new and exciting branch of Computer Science. It is not only the concern of Computer Science but also of other fields such as Philosophy, Linguistics, Cognitive Science, Mathematics and Engineering. This article seeks to explain what Al is, its history and how it is different from conventional disciplines of Computer Science.